Wide-field piecemeal cold snare polypectomy of large sessile serrated polyps without a submucosal injection is safe - Tate, David J.; Awadie, Halim; Bahin, Farzan F.; Desomer, Lobke; Lee, Ralph; Heitman, Steven J.; Goodrick, Kathleen; Bourke, Michael J. (Endoscopy, 2018)
Background and study aims Large series suggest endoscopic mucosal resection is safe and effective for the removal of large (≥ 10 mm) sessile serrated polyps (SSPs), but it exposes the patient to the risks of electrocautery, including delayed bleeding. We examined the feasibility and safety of piecemeal cold snare polypectomy (pCSP) for the resection of large SSPs.Methods Sequential large SSPs (10 – 35 mm) without endoscopic evidence of dysplasia referred over 12 months to a tertiary endoscopy center were considered for pCSP. A thin-wire snare was used in all cases. Submucosal injection was not performed. High definition imaging of the defect margin was used to ensure the absence of residual serrated tissue. Adverse events were assessed at 2 weeks and surveillance was planned for between 6 and 12 months.Results 41 SSPs were completely removed by pCSP in 34 patients. The median SSP size was 15 mm (interquartile range [IQR] 14.5 – 20 mm; range 10 – 35 mm). The median procedure duration was 4.5 minutes (IQR 1.4 – 6.3 minutes). There was no evidence of perforation or significant intraprocedural bleeding. At 2-week follow-up, there were no significant adverse events, including delayed bleeding and post polypectomy syndrome. First follow-up has been undertaken for 15 /41 lesions at a median of 6 months with no evidence of recurrence. Conclusions There is potential for pCSP to become the standard of care for non-dysplastic large SSPs. This could reduce the burden of removing SSPs on patients and healthcare systems, particularly by avoidance of delayed bleeding.